A Legal Consequences of the Passing Off Practice of the MS GLOW Brand by the PSTORE GLOW Brand - Wibowo, Rezqiyan Bagus (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2024)
Intellectual Property Rights are essentially rights with special and special characteristics because these rights are granted by the State. A brand as an Intellectual Property Right is basically a sign to identify the origin of goods and services from a company with the goods and/or services of another company. One of the cases regarding Passing Off occurred in the Commercial Court Decision at the Medan District Court Number 2/Pdt.Sus-HKI/Merek/2022/PN Niaga Mdn. It started when Shandy Purnamasari filed a trademark cancellation lawsuit against PT PSTORE Glow Bersinar Indonesia. This lawsuit is based on the similarity of the brands